Toll-like Receptors: Roles in Infection and Neuropathology - Tammy Kielian (2009)
Mammalian Toll-like receptors (TLRs) were first identified in 1997 based on their homology with Drosophila Toll, which mediates innate immunity in the fly. Over the past eight years, the number of manuscripts describing TLR expression and function in the central nervous system (CNS) has been increasing steadily and expanding beyond their traditional roles in infectious diseases to neurodegenerative disorders and injury. Interest in the field serves as the impetus for this volume in the Current Topics in Microbiology and Immunology series entitled Toll-Like Receptors: Roles in Infection and Neuropathology. The first five chapters highlight more traditional roles for TLRs in infectious diseases of the CNS. The second half of the volume discusses recently emerging roles for TLRs in noninfectious neurodegenerative diseases and the challenges faced by these models in identifying endogenous ligands. Several conceptual theories are introduced in various chapters that deal with the dual nature of TLR engagement and whether these signals favor neuroprotective versus neurodegenerative outcomes.